Dampak Sosialisasi Perpajakan, Tarif Pajak dan Pemahaman Perpajakan terhadap Kepatuhan Wajib Pajak - Daud, Dahniyar; Arif Mashuri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This research aims to test and analyze the influence of tax socialization, tax rates and understanding of taxation simultaneously or partially on the compliance of SME taxpayers registered at the Makassar City Cooperatives and SMEs Office. This type of research is explanatory research with a quantitative approach method. The sample used was 80 SME respondents who were registered with the Makassar City Cooperatives and SMEs Department. Data sources consist of primary data and secondary data with data collection methods, namely distributing questionnaires to respondents and recording documentation. The data analysis techniques used are descriptive statistical analysis, inferential statistical analysis, and multiple linear regression analysis. The results of this research state that Tax Socialization, Tax Rates and Tax Understanding have a significant effect on taxpayer compliance.